Contents hormone cortisol in the blood youths with different levels of physical training and its changes in the single training sessions under athleticism - Chernozub A.A (Kharkov National Pedagogical University, 2011)
Obtained and summarized the results of studies indicate that the content of the hormone cortisol when exposed to body exercise power orientation exhibits rapid reaction type, which have no signs of consolidation over the three years of occupation by force sports. The studies found that reducing the amount of cortisol in the blood, fixed after the training load in all four study groups, showing a certain dependence on the magnitude and intensity of training loads, and possibly on the level of fitness.